Towards Malaysian sign language database - Maarif, Haris Al Qodri; Bilal, Sara Mohammed Osman Saleh; Akmeliawati, Rini (IIUM Press, 2011)
Sign language is the verbal language for the people who have hearing impairment. Those people who have those kinds of problems are widely known as the deaf people. Basically the word of deaf is referred into two; the Deaf (with capital D) is the hearing impairment person who understands sign language and the deaf (with small d) is the person who does not have capability in understanding the sign language. In this article, the "deaf' (with small d) will be used to cover the entire people with hearing impairment and disability